P.118 An experience with combined cerebral oximetry and stump pressure measurement to guide shunt insertion during carotid endarterectomy. (17th June 2016) - Kesarwani, R; Findlay, M
Abstract : Background: Cross-clamp ischemia during carotid endarterectomy (CEA) can cause perioperative stroke. Selectively shunting patients based on intraoperative monitoring modalities that assess risk for ischemia can reduce the occurrence of immediate stroke. An experience with combined cerebral oximetry and stump pressure measurement to direct selective shunting is presented here.Methods: Study comparing intraoperative monitoring data, the decision to shunt, and presence of immediate post-operative deficits. Patients were shunted if either cerebral oxygen saturation dropped by more than 10% by cerebral oximetry, or stump pressure during cross-clamping was less than 40 mmHg. Cross-clamp ischemia was determined by the presence of ipsilateral neurological deficit upon awakening.Results: 245 patients were included in this study. 22% were shunted. Patients who were not shunted were significantly more likely to have collateral blood flow detected on angiography. Immediate post-operative stroke was not encountered in any of the patients included in the study. One patient who met shunting criteria but was excluded since he could not have a shunt inserted due to difficult anatomy did suffer stroke.Conclusions: With the dual-monitoring criteria presented here, 22% of patients were shunted. With the exception of one patient who could not have a shunt placed, no immediate post-operative stroke was encountered.